Discovery of a series of 1H-pyrrolo[2, 3-b]pyridine compounds as potent TNIK inhibitors. (1st February 2021) - Yang, Bowen; Wu, Qian; Huan, Xiajuan; Wang, Yingqing; Sun, Yin; Yang, Yueyue; Liu, Tongchao; Wang, Xin; Chen, Lin; Xiong, Bing; Zhao, Dongmei; Miao, Zehong; et al.
Graphical abstract: Abstract: In an in-house screening, 1 H -pyrrolo[2, 3- b ]pyridine scaffold was found to have high inhibition on TNIK. Several series of compounds were designed and synthesized, among which some compounds had potent TNIK inhibition with IC50 values lower than 1 nM. Some compounds showed concentration-dependent characteristics of IL-2 inhibition. These results provided new applications of TNIK inhibitors and new prospects of TNIK as a drug target.